Respuesta :
Hello! To eliminate the value of y, lets multiply the first equation by 2 and then add the two equations together:
[tex]-8x-4y=-24[/tex]
[tex]2x+4y=-12[/tex]
The resulting equation would be: [tex]-6x=-36[/tex]
Solving the equation, we'll get the value of x which is 6.
Lastly, we plug in the value of x to any of the equations to get the value of y. Let's plug it into the first equation.
[tex]-4(6)-2y=-12[/tex]
[tex]-24-2y=-12[/tex]
[tex]-2y=12[/tex]
[tex]y=-6[/tex]
ANSWER: Therefore, the solution to the system is the ordered pair (6,-6).
[tex]-8x-4y=-24[/tex]
[tex]2x+4y=-12[/tex]
The resulting equation would be: [tex]-6x=-36[/tex]
Solving the equation, we'll get the value of x which is 6.
Lastly, we plug in the value of x to any of the equations to get the value of y. Let's plug it into the first equation.
[tex]-4(6)-2y=-12[/tex]
[tex]-24-2y=-12[/tex]
[tex]-2y=12[/tex]
[tex]y=-6[/tex]
ANSWER: Therefore, the solution to the system is the ordered pair (6,-6).